Inventário cultural do Quilombo Alto Santana : na última rua, o início de tudo - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This technical report is the result of the research called “Cultural Inventory of the Alto Santana Quilombo: in the last street, the beginning of everything, with the aim of producing knowledge about the cultural heritage of the Alto Santana Quilombo, based on the significant cultural references for the formation of the identity and collective memory of that community, which is located on the periphery of the historical center City of Goiás-GO. We set out with the question: What are the cultural expressions, their works and crafts that are recognized by the community as being a legacy of their ancestry and that they consider to be cultural heritage? Our methodological approach was actionresearch, in which we immersed ourselves in the daily life of the community, building bonds of trust, making the stages of the research more flexible and seeking the involvement of the people taking part in the process. We are guided by a theoretical framework committed to breaking with the colonial conception of heritage identification; assuming a decolonial perspective; giving voice to silenced memories through the participation of the community in the process of identifying the cultural references it recognizes as local cultural heritage. To achieve this goal, we used the inventory methodology, in which the cultural references identified were categorized as: places, knowledge, celebrations, objects and forms of expression. Interviews, conversation circles and a documental survey were the main sources for collecting information, systematizing and interpreting data. As a way of giving visibility to the information gathered, a website was developed as a product of the research, hosting information on both the cultural manifestations identified and the history of the quilombo's constitution process, as well as the personalities identified as those bearing the knowledge of its history and the narrative to pass it on to new generations. It is hoped that this study and its product will be democratically accessed and used by the community, as instruments that contribute to strengthening and making visible the history of the Alto Santana Quilombo, its cultural heritage, its forms of expression and resistance in the face of the struggle for reparation for the historical inequalities that the black population has been subjected to, not only in the City of Goiás, but in Brazil.
Cultural Inventory of the Alto Santana Quilombo : in the last street, the beginning of everything
Keywords: Patrimônio; Decolonialidade; Inventário cultural; Quilombo; Silenciamento; Memória; Heritage; Decoloniality; Cultural inventory; Silencing; Memory; CIENCIAS HUMANAS::HISTORIA; HISTORIA::HISTORIA DO BRASIL